Directive Speech Acts in English Classroom Instruction for First Grade Students at SDUT Bumi Kartini Jepara - Eliza Naili Agustin; Santi Adriyani (Journal of English Language Teaching and Linguistics, 2026)
This study investigates the directive speech acts employed by the English teacher during classroom interaction. Specifically, it analyzed their types and forms and identified the dominant patterns of use throughout the teaching and learning activities. This study used a qualitative descriptive design. Data were collected through classroom observations, video recordings, interviews, and field notes in the first-grade English class of the International Primary Class (IPC) at SDUT Bumi Kartini Jepara. Data analysis followed the interactive model developed by Miles & Huberman (1984), encompassing the processes of data condensation, data display, and conclusion drawing and verification. The findings revealed that the teacher employed five types of directive speech acts in classroom interaction, including commands, requests, suggestions, advice, and prohibitions. Among these types, commands were the most dominant, with 46 occurrences (57.5%). This study also identified two forms of directive speech acts, namely directives and indirect forms. Among these forms, direct speech acts were more dominant, occurring 53 times (66.25%). These findings indicate that the effective use of directive speech acts supports classroom interactions and supports effective English teaching at the elementary school level. The findings contribute to pragmatic studies by providing empirical evidence on the use of directive speech acts in English classroom interaction at the elementary school level. Practically, the findings provide insights for English teachers in selecting and employing appropriate directive speech acts to facilitate effective classroom communication and support students' engagement in the learning activities.